Physical Activity (PA): Current Conditions and Correlation with Literacy and Numeracy in Elementary School Students at Pontianak City (Journal of Physical Education Health and Sport, 2022)
The purpose of this study was to identify the level of physical activity of students and then to analyze the types of physical activity carried out to support literacy and numeracy skills and to examine the relationship between physical activity and students' literacy and numeracy skills. The method used in this research is mixed methods and implemented using a concurrent triangulation design. The instruments used were PAQ-C (Physical Activity Questioner for older Children), interview guide sheets and literacy and numeracy test sheets. The results of the interviews show that various physical activities are carried out by students at school and at home such as playing ball which is played with the feet or thrown by hand, chasing games, aquatic activities such as playing in the pool, playing roles, rubik's cube, robots and assembling puzzles. Of all these activities, it turned out that they were not structured and directed towards activities that support literacy and numeracy skills, as well as their type and duration. Physical activity data also shows that 58.54% of students are currently at a low level of physical activity and the remaining 41.47% are at a high activity level, this is adjusted to the interpretation of the data using PAQ-C. Based on the correlation test between literacy and numeracy skills and physical activity, it turns out that there is a positive relationship between the variables and the sig. (0.0000.05).